Enhanced mineralization of atrazine by surface induced hydroxyl radicals over light-weight granular mixed-quartz sands with ozone. (1st February 2019) - Wang, Da; Xu, Haodan; Ma, Jun; Giannakis, Stefanos; Lu, Xiaohui; Chi, Huizhong; Song, Shuang; Qi, Jingyao
Abstract: A light-weight granular mixed-quartz sand (denoted as L-GQS) combined with stirring-assisted bubble column reactor was firstly applied in catalytic ozonation of atrazine. The L-GQS, with a density of 2.36 g cm −3 and average diameter of ca. of 4 mm, was readily churned up and uniformly distributed within the solution in the reactor. The introduction of L-GQS was found to exhibit enhanced catalytic ozonation of atrazine, with the increase in degradation rate and the dissolved organic carbon (DOC) removal being more than 2-fold for the catalytic process (L-GQS dosage = 5 g L −1, [atrazine]0 = 50 μM, [O3 ] = 25 mg L −1, gas flow = 0.2 L min −1, at pH 7.0 and 293 K). The L-GQS settled at the bottom of the reactor after experimentation, allowing its easy separation from the solution. A complete characterization of the material (XRD, XPS, FTIR, FE-SEM/EDS, BET and pHpzc ) revealed that L-GQS consisted of α-quartz, β-cristobalite, anorthoclase and small amount of iron oxy-hydroxides. Hydroxyl groups, Bronsted acid sites and Lewis acid sites on the surface of L-GQS all contributed to the atrazine adsorption, ozone decomposition and ·OH generation. The L-GQS catalyzed ozonation exhibited superior atrazine degradation and mineralization rates in a wide range of pH (3.0–9.0) and reaction temperatures (278 K–293 K). Also, an enhancement of DOC abatement was observed both in presence of natural organic matter isolates and natural water matrices (river water) when L-GQS was used. Finally, the degradation mechanism was proposed, based on the intermediates and by-products formation analyzed by LC-QTOF-MS/MS and ionic chromatography. Our results indicate that the L-GQS combined with stirring-assisted bubble column reactor could be utilized as an enhancement of ozone-based advanced oxidation processes. Graphical abstract: Image 1 Highlights: L-GQS is an effective ozonation catalyst for pollutants mineralization. The chemical and physical properties of L-GQS were characterized in detail. L-GQS revealed excellent ·OH generation capacity in wide range of conditions. L-GQS can be easily dispersed and separated from solution.